International standards of legal status of judge - Dashkevich, Serhii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2022)
The article analyzes international legal acts regulating the legal status of judges, as well as containing standards of proper justice. Among them, the author highlights the conventions and pacts of the UN and the Council of Europe, ratified by Ukraine and which contain norms that are binding on the national level. The second group is made up of the norms-recommendations of the Council of Europe and international judicial associations, the implementation of which is a moral obligation of the state. The attention is focused on the problem of renewing public confidence in the court and ensuring justice in accordance with generally recognized international human rights standards, which is a sign of a democratic system.The conclusions state that the reform of the judiciary necessitates the consideration of international standards of justice. These international acts contain numerous norms that define the role of judges in the administration of justice and determine the features of their legal status. This is quite natural, because justice is the most important guarantee of protection of the rule of law, fundamental human rights and freedoms and the values of a democratic society. We agree with the opinion of V. Kuzmuk that «judicial reform processes should be built, first of all, through the implementation of general international principles of justice and rules of conduct of judges in national legislation. That is, the priority of draft law in this direction should be the analysis of the basic ideas of justice, laid down in international legal practice, and their basis for such a reform». Such steps should be aimed at ensuring the greatest guarantees of the competence, independence and impartiality of judges necessary to strengthen the rule of law and to protect the rights and freedoms of the individual in a democracy.